2006
DOI: 10.2174/156720206778018776
|View full text |Cite
|
Sign up to set email alerts
|

Role of Taurine in Spinal Cord Injury

Abstract: Taurine is a sulfur amino acid. It is found endogenously in human and several others tissues. It is significantly in high concentration in mammals. Human body contains about 0.1% of body weight as taurine. It has a number of physiological and pharmacological actions. It is also used in the therapy of important organs dysfunctions. In spinal cord it has inhibitory effects; like antiepileptic and anti-nociceptive. Taurine also inhibits substance p induced biting and scratching behavior. In spinal cord injury ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Similarly, Li et al (2016) observed significant increase in lysozyme activity of yellow catfish (Pelteobagrus fulvidraco). Therefore, these results indicate that taurine not only can improve health and immunity of mammals (Kingston et al 2004;Gupta et al 2006), but also can improve the health and innate immunity of fish. IGF-1 mRNA expression was assessed in this study as a new parameter to determine whether taurine supplementation might have effect on gene expression.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Similarly, Li et al (2016) observed significant increase in lysozyme activity of yellow catfish (Pelteobagrus fulvidraco). Therefore, these results indicate that taurine not only can improve health and immunity of mammals (Kingston et al 2004;Gupta et al 2006), but also can improve the health and innate immunity of fish. IGF-1 mRNA expression was assessed in this study as a new parameter to determine whether taurine supplementation might have effect on gene expression.…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, our results showed that IGF-1 mRNA expression level was significantly increased by 1.5% taurine supplementation. Some studies have been conducted to determine whether taurine supplementation could affect fish at gene expression level (Kingston et al 2004;Gupta et al 2006). The function of IGF-1 in fish is similar to that in human or mammals, and IGF-1 can only exert nutritional regulation in the liver of fish (Duan et al 1994;Duan 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Taurine protection has been found also in cells damaged by b-amyloid and bilirubin. Some taurine cell protection is also reported during ischemia-reperfusion [12], tissue crushing [13], fibrosis [14] and exposure to light [15]. Cytoprotective actions of taurine have been examined in different organs, particularly lung, liver, heart, brain and kidney, but some studies also report taurine protective actions in spinal cord, urinary bladder, retinal pigment epithelium, erythrocytes, and stomach.…”
Section: Protective Actions Of Taurinementioning
confidence: 99%
“…Since taurine levels recorded in CSF of pathological gamblers are very high, consideration of its involvement is warranted. In several cases where taurine level was recorded to be elevated, the increase reflected greater involvement of taurine in protective mechanisms and in such situations exogenous addition of taurine provided additional benefits [12,14]. There is a long list of potential actions for taurine In the CNS, with moderate to significant effects.…”
Section: Amino Acids As a Cause For And Source Of Pharmacotherapymentioning
confidence: 99%
“…In PG too there is alternation in their concentrations. Taurine which is synthesized from cystein has a wide spectrum of central actions, from anticonvulsant to anti-aggressive and anti tremor to many more [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%